(untitled) (Scientiae Studia, 2006)
This paper propose a new socio-epistemic context to discuss the problems that act upon the interaction between science and society. Using the idea of implication, and the analysis of the social impact of science, I propose some conceptual distinctions that I consider useful to gain consensus in science, technology and society matters. I highlight the pragmatic dimension of decisions involved and the importance of institutional context to legitimate them and affront corresponding responsibilities. The implication context may facilitate taking collective decisions once one understand the need to discuss at the same time the many faces of the problems involved. In substance those faces changes in many ways if we consider matters related to the efficacy or the legitimacy of scientific practices.